FIKIH: ANALISIS PERNIKAHAN DINI MENURUT PANDANGAN 4 MAZHAB - Purnomo, Agus; Hani, Umi; Hadi, Abdul; Zahra Maulida, Atika (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2025)
the phenomenon of early marriage is still widely found, especially in areas where the majority of educational awareness is still relatively low. The trend of early marriage is still a pro and con. There are also parents who want their children to graduate from school, become adults or be established first. There are concerns about failing their studies, getting divorced quickly because they are not old enough and the economy is difficult because they do not work. Research Objectives To find out the Fiqh View on early marriage according to the 4 Schools. This research method uses a descriptive qualitative method. This study uses a qualitative descriptive analysis, namely an analysis carried out through field studies to Ulama, Society, and the MUI of Banjarmasin City in collecting data using the purposive sampling research method. The purposive sampling method is a study conducted to take research samples in the field that have been determined based on the desired sample information, the interview technique uses a structured interview technique